Working with bacteria and putting bacteria to work: The biopolitics of synthetic biology for energy in the United Kingdom - McLeod, Carmen; Nerlich, Brigitte; Mohr, Alison (Elsevier, 2017)
The UK government has made significant investment into so called ‘fourth-generation’ biofuel technologies. These biofuels are based on engineering the metabolic pathways of bacteria in order to create products compatible with existing infrastructure. Bacteria play an important role in what is promoted as a potentially new biological industrial revolution, which could address some of the negative environmental legacies of the last. This article presents results from ethnographic research with synthetic biologists who are challenged with balancing the curiosity-driven and intrinsically fulfilling scientific task of working with bacteria, alongside the policy-driven task of putting bacteria to work for extrinsic economic gains. In addition, the scientists also have to balance these demands with a new research governance framework, Responsible Research and Innovation, which envisions technoscientific innovation will be responsive to societal concerns and work in collaboration with stakeholders and members of the public. Major themes emerging from the ethnographic research revolve around stewardship, care, responsibility and agency. An overall conflict surfaces between individual agents assuming responsibility for ‘stewarding’ bacteria, against funding systems and structures imposing responsibility for economic growth. We discuss these findings against the theoretical backdrop of a new concept of ‘energopolitics’ and an anthropology of ethics and responsibility.